Development and Evaluation of Puerarin Loaded-Albumin Nanoparticles Thermoresponsive in situ Gel for Ophthalmic Delivery - Hu L; Xu Y; Meng H (Dove Medical Press, 2022)
Lixiu Hu,1,* Yong Xu,2,* Hui Meng3 1Department of Pharmaceutical, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People's Republic of China; 2Department of Pharmaceutical, Shanghai Punan Hospital of Pudong New District, Shanghai, People's Republic of China; 3Department of Pharmaceutical, 905 Hospital of People's Liberation Army, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Hui Meng, Email Menghui0801@163.comPurpose: Puerarin (PUR) is a major bioactive ingredient extracted from the root of Pueraria lobata (Willd.) Ohwi, which is known as Gegen in traditional Chinese medicine. Conventional PUR ophthalmic dosage forms such as solutions and suspensions have many drawbacks, including-rapid precorneal elimination of the drug mainly due to lacrimal duct drainage. The purpose of this study is to develop a thermal responsive in situ gel system containing PUR-loaded human albumin nanoparticles (PUR-HSA-NPs ISG).Methods: The system has the required sol-gel phase transition temperature, and therefore can be used for local ocular administration to treat glaucoma. The formulation was evaluated for its sol-gel transition temperature, viscosity and in vitro release. In vivo eye irritation was evaluated in rabbits. In this study, the animal model of glaucoma was used to evaluate the pharmacodynamics of PUR-HSA-NPs ISG in vivo.Results: Morphologically, the PUR-HSA-NPs ISG exhibited a normal spherical shape with no aggregation or degradation. It had a mean size of 64.8 nm, and the drug-loading and encapsulation efficiency were 7.1%± 0.3% and 80.7%± 7.4%, respectively. The gelation temperature of the prepared PUR-HSA-NPs ISG thermogelling solutions was 37°C. Meanwhile, the PUR-HSA-NPs ISG showed thixotropic behavior with the downward curve exhibiting lower shear stress values as compared to corresponding points on the upward curve. The pharmacological results showed a continuous reduction of the IOP value for a long time and that the value remained in a lower-level range compared to that in the PUR eye drop group. According to the pharmacodynamic results, the Bcl-2/Bax ratio of the PUR-HSA-NPs ISG group was closest to 1 (0.8798, 24 h), with obvious reduction of tissue cell apoptosis.Conclusion: Through this study, it was found that PUR-HSA-NPs ISG is an ideal ocular drug delivery system. It is hoped that this product could be further promoted for clinical applications in the future.Keywords: puerarin, albumin nanoparticles, thermoresponsive in situ gel, ophthalmic delivery